Dampak Locus of Control dan Komitmen Profesional terhadap Perilaku Etis Auditor dalam Situasi Konflik - Ratnawati, Made Mega; Budiartha, I Ketut (E-Jurnal Akuntansi; Vol 31 No 4 (2021)DO - 10.24843/EJA.2021.v31.i04.p02, 2021)
This study aims to determine the effect of locus of control and professional commitment on auditor’s ethical behavior in conflict situations. This research was conducted at a public accounting firm (KAP) in Bali. The sample used in this study amounted to 40 and in its determination using simple random sampling technique. The data analysis technique used multiple linear regression analysis and data collection was done using a questionnaire. Based on the analysis, it was found that locus of control and professional commitment had a positive effect on auditors' ethical behavior in conflict situations. This shows that auditors who have self-confidence in their profession can behave ethically when making decisions in conflict situations. Keywords: Locus of Control; Professional Commitment; Auditor Behavior.